2015
DOI: 10.1097/qai.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HIV Status in African Adults With Discordant HIV Rapid Tests

Abstract: Background In resource-limited settings, HIV infection is often diagnosed using two rapid tests. If the results are discordant, a third tie-breaker test is often used to determine HIV status. This study characterized samples with discordant rapid tests and compared different testing strategies for determining HIV status in these cases. Methods Samples were previously collected from 173 African adults in a population-based survey who had discordant rapid test results. Samples were classified as HIV positive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported using a suboptimal testing strategy that differed from the WHO recommendations [5,8,1114,16,2230,3234,36–39,4244,49,51,53,59,62,64–66,68,72,75]. Suboptimal testing strategies included using a highly specific first-line test and highly sensitive second-line test [14,33,39,55], using a single RDT for HIV-positive diagnoses [11,66,72], using a high prevalence testing strategy in a low prevalence setting [16,49], using a parallel testing algorithms and a tiebreaker testing strategy (where a third assay is used to resolve discrepant test results and rule in HIV infection) [5,12,13,16,24,25,2730,32,34,36,37,68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,16,17 False-negative HIV rapid tests and false-recent incidence assays could also compromise population-level surveys of HIV infection. 22 In these settings, false-negative rapid tests may underestimate HIV prevalence, and false-recent incidence assays may overestimate HIV incidence.…”
Section: Introductionmentioning
confidence: 99%